Students’ Responses to Multi-Modal Emergency Remote Learning During COVID-19 in a South African Higher Institution - Obert Matarirano; Onke Gqokonqana; Abor Yeboah (Research in Social Sciences and Technology- OpenED Network, 2021)
COVID-19 pandemic forced several higher education institutions (HEI) to operate remotely. Emergency remote teaching, using synchronous and asynchronous instruction, was adopted by several HEIs. The experiences of students with remote teaching and learning in certain situations are not fully understood, thus need to be explored. This study explored the experiences of students with the emergency remote teaching and learning practices adopted at a selected HEI in South Africa. A cross-sectional and self-administered survey was used to gather data from 243 conveniently sampled returning students within the Department of Accounting and Finance. Descriptive statistics were used to make sense of the collected data. The study found that students preferred a face-to-face approach to learning to remote learning. The respondents underscored insufficient data, unstable network connection, unconducive home environments and loneliness as deterrents to effective remote learning. Despite these negative experiences, students appreciated the flexibility and convenience of recorded video lectures and acknowledged the compassion and support of lecturers during remote learning. An understanding of the experiences of students during remote learning provides a basis for future teaching plans, which would improve students' learning experiences. In its current format and students living in their home environments, remote learning greatly diminishes the chances of success for most students. Lecturers need to be compassionate and considerate of student’s struggles in their plans for remote teaching and learning as well as online learning.